STUDI AWAL PENGEMBANGAN JARINGAN INKUBATOR TEKNOLOGI & BISNIS PADA INSTITUSI PENDIDIKAN TINGGI DI INDONESIA - W Widayat; Settings Irawadi Jamaran (LPPM Universitas Terbuka, 2009)
Partnership development and technology business incubator on the basis of mutual interests will require more real if developed until the stage of commercialization of technological innovation in the markerplace. The partnership is based on sharing information, experiences and resources between hinger education institutions, research institutions and the community. It is expected that such partership will preduce new business organization that comes from new ideas and new entrepreneurs. In this paper the initial design model is given as networks center college of growth in the form of partnership networks of higher education institutions and research institutions that support the development needs of the community business organizations through technology and business incubators.